1995
DOI: 10.7326/0003-4819-122-10-199505150-00005
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of cepacia Respiratory Tract Colonization and Infection Associated with Nebulized Albuterol Therapy

Abstract: Multiple-dose medications and reliance on benzalkonium chloride as a medication preservative provide a mechanism for nosocomial spread of microorganisms, particularly if infection control procedures are not carefully followed. Repetitive-element PCR is a useful fingerprinting technique for molecular epidemiologic studies of B. cepacia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 0 publications
0
58
0
4
Order By: Relevance
“…Six 20 ml vial of albuterol solution 0.5 % and held at room temperature. One ml samples were cultured before inoculation and on days 2 and 7 after inoculation as described above.…”
Section: Methods Case Definition and Ascertainmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Six 20 ml vial of albuterol solution 0.5 % and held at room temperature. One ml samples were cultured before inoculation and on days 2 and 7 after inoculation as described above.…”
Section: Methods Case Definition and Ascertainmentmentioning
confidence: 99%
“…Our investigation indicated that B. cepacia respiratory acquisition was associated with receipt of nebulized medications. This outbreak and the recent report of B. cepacia respiratory acquisition linked to extrinsic contamination of albuterol solution emphasize the potential for microbial contamination of nebulized medications despite the presence of the preservative benzalkonium chloride [20]. The administration of nebulized medications should be done carefully, using standard administration techniques and disinfection practices.…”
Section: Administration Of Nebulized Medicationsmentioning
confidence: 95%
See 3 more Smart Citations